Article Effect of Fuel Quality, Vehicle Maintenance and Advanced Emission Control Technology on Pakistan In -Use Light Vehicle Emissions - Taimoor, Aqeel (Journal of King Abdulaziz University: Engineering Sciences, 2023)
Pakistan is suffering from some of the worst air quality in Asia. The transportation sector is a major contributor to air pollution along diesel powered vehicles and rickshaws being the primary pollutions source. However, the contribution from light duty vehicles cannot be ignored. In this paper, results from an in-use emission study of over 500 light duty vehicles are reported and discussed. A random geographically diversified survey is conducted to collect data regarding the emissions from in-use vehicles in Pakistan. A review of the government fuel quality policy is provided. Through this analysis, the effects of polices addressing vehicle maintenance and repair, advanced vehicle emission technology and fuel quality are evaluated. These results provide insight to guide further measures to ensure meaningful impact on urban air quality in Pakistan. The same study may also be conducted in other regional countries to support effective emission control policy from the light vehicles.